Environmental Tax Reform, R&D Subsidies and CO2 Emissions: View Double Dividend Hypothesis - Hong, Cheng-Yih; Huang, Chung-Huang; Li, Jian-Fa; Tsai, Yi-Chi (International Journal of Energy Economics and Policy, 2018)
This study investigated whether environmental taxes achieve the double dividend of coexistence of economic growth and environmental protection. The research method used dynamic industrial relations models to estimate the influence of environmental taxes influence on the economy and environment. The goal was to conduct an objective analysis with scientific data. The conclusions provide a clue indicating that environmental taxes could only be used to facilitate short-term coexistence between economic growth and environmental protection. Once entering the mid-term and long term, the lack of innovation and technical progress would eventually cause economic development and environmental protection to diverge, which is why studies are yet to reach a consensus. The results suggest that although using environmental taxes to promote economic development and environmental protection can achieve the double dividend in the short term, in the midterm, the first dividend disappears unless a solution for improved energy efficiency and technical innovation can be determined immediately. Furthermore, to sustain its economic development and environmental protection efforts, Taiwan must first optimize its industrial structure, which can only be achieved through advanced research and development. Keywords: Environmental Tax Reform, R&D Subsidies, CO2 Emissions, Double Dividend Hypothesis JEL Classifications: C67, D57, Q50, Q58